When committed and open-minded people come together to make gender research work - Mulema, Annet A. (International Livestock Research Institute, 2016)
Under the gender initiative, Annet Mulema has supported three projects, two of which were completed successfully, and one less so. Gender specialists support non-gender scientists to collect and analyse gender-disaggregated data. They pay attention to decision-making, household relations, and access and control of resources. Some projects are more successful than others: it helps to have the commitment of the principal investigator and from other non-gender scientists.